2020
DOI: 10.1029/2020ea001175
|View full text |Cite
|
Sign up to set email alerts
|

GLOBE Observer Data: 2016–2019

Abstract: This technical report summarizes the GLOBE Observer data set from 1 April 2016 to 1 December 2019. GLOBE Observer is an ongoing NASA‐sponsored international citizen science project that is part of the larger Global Learning and Observations to Benefit the Environment (GLOBE) Program, which has been in operation since 1995. GLOBE Observer has the greatest number of participants and geographic coverage of the citizen science projects in the Earth Science Division at NASA. Participants use the GLOBE Observer mobi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…GLOBE is an international science and education program engaging students, teachers, community members and scientists in environmental monitoring and research. Created 25 years ago to support inquiry-based learning in K-12 classrooms, GLOBE recently expanded its mission to support citizen scientist data collection and investigation by launching the GLOBE Observer mobile app, a place-based citizen science app for volunteers of all ages (Amos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…GLOBE is an international science and education program engaging students, teachers, community members and scientists in environmental monitoring and research. Created 25 years ago to support inquiry-based learning in K-12 classrooms, GLOBE recently expanded its mission to support citizen scientist data collection and investigation by launching the GLOBE Observer mobile app, a place-based citizen science app for volunteers of all ages (Amos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For the most part, the protocols-clouds, mosquito habitats, land cover, trees, and eclipse-do not require equipment beyond the app tools to collect meaningful data. The eclipse protocol requires a thermometer and trees has an optional tree circumference observation that requires a tape measure (Amos et al 2020). Training for these protocols is provided within the app.…”
Section: The Globe Programmentioning
confidence: 99%
“…Since the primary data are geotagged photos, location accuracy is the most significant data quality check done on the GO on a Trail data to facilitate mapping the photos to other LCLU data. Further, a published quality assessment of all GLOBE Observer land cover data collected between 2016 and 2019, including GO on a Trail data, found that location errors are the most common errors (Amos et al, 2020). The GLOBE Observer app reports location accuracy estimates based on repeated queries of the phone's GPS receiver.…”
Section: Data Quality Analysismentioning
confidence: 99%
“…Bayas et al (2020) report significant improvement in the quality of volunteers' land cover classifications when users were provided with timely feedback. As documented in Amos et al (2020), GLOBE Observer provides such feedback for volunteers who submit clouds data. Volunteers are encouraged to take cloud observations when a satellite is overhead through an alert that appears 15 min before the overpass.…”
Section: Data Quality Analysismentioning
confidence: 99%
See 1 more Smart Citation